Prevalence and Prognostic Significance of Liver Fibrosis in Patients With Aneurysmal Subarachnoid Hemorrhage - Li, Tiangui; Wang, Peng; Gong, Xiao; Chong, Weelic; Hai, Yang; You, Chao; Kang, Juan; Fang, Fang; Zhang, Yu (Frontiers in Neurology, 2022)
Objectives:To report the prevalence, clinical associations, and prognostic consequences of liver fibrosis in patients with aneurysmal subarachnoid hemorrhage (aSAH) Methods: In a retrospective study of patients with aSAH, we evaluated three validated liver fibrosis indices modeled them as continuous exposure variables, including the Aspartate Aminotransferase/Platelet Ratio Index (APRI), the Fibrosis-4 (FIB-4) index, and the Forns index. The primary outcome is mortality at 90 days. We compared the addition of fibrosis indices to the predictors of the full Subarachnoid Hemorrhage International Trialists model. Results: A total of 3722 patients with aSAH were included in the study. According to the APRI, FIB-4 index , and Forns index , 21.7%, 17.7%, and 11.4% of patients have liver fibrosis. After adjusting for potential confounding factors, liver fibrosis was associated with increased 90-day mortality, with odds ratios 1.35 (95% CI 1.02-1.77 ) for FIB-4 index, 1.39 (95% CI .08-1.78) for APRI, and 1.53 (95% CI 1.11-2.12 ) for Forns index. Similarly, liver fibrosis was associated with an increased risk of rebleeding for all three fibrosis indices. However, the Forns index was not significantly associated with mortality and rebleeding. The addition of FIB-4 indices and APRI into the standard model improved mortality prediction. Conclusions: Liver fibrosis is common in patients with aSAH and is associated with mortality and rebleeding. The addition of liver fibrosis indices to a standard clinical model significantly improves risk stratification.